INCIDENCES OF ACUTE APPENDICITIS CAUSED BY VARIOUS PARASITES WITHIN KIRKUK PROVINCE, IRAQ - Bazzaz, Ayoub A.; Shaaban, Ruwaida E.; Kopurlu, Sa’ad A.Y.; Al-Basheer, Nada T.; Chelebi, Noorhan A. (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Acute appendicitis (AA) may initiate due to various agents including bacteria, parasites, mainly Enterobius vermicularis and others meanwhile studies on its etiology are so rare in Iraq. Method: This research involves 50 specimen undergone appendectomies presented with clinical symptoms of AA investigated for various parasites. Results: Four different parasites with various proportions were detected in the 50 appendectomies patients. Almost 27(54%) of cases were diagnosed negative or non-parasitic infection while only 23(46%) were diagnosed infected with various parasites e.g. Entamoeba histolytica, with highest prevalence 12(24%); followed by Enterobius vermicularis with 8(16%); Blantidium coli 2(4%) and finally Ascaris lumbricus 1(2%). Novelty: The percentage of infection by E. vermicularis denotes the highest international record as the main cause of acute appendicitis worldwide which might be interpreted as a most pandemic parasite in poor food hygiene conditions in Iraq. Appendicitis displayed almost no impact on blood parameters. Extra parameters should be adopted to monitor the hygiene of Iraqi local restaurants or takeaways serve the exposed food for public consumption.